2001
DOI: 10.1081/clt-100102880
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Acute Carbon Monoxide Poisoning in a Spanish Region

Abstract: Compared with previous Spanish series or with the antecedent year, acute carbon monoxide poisoning has a high prevalence in our region. Two factors appear to be essential to the accurate diagnosis of acute carbon monoxide poisoning: 1) the ability of emergency room physicians to recognize the clinical symptoms of carbon monoxide poisoning and 2) access to a carbon monoxide-oximeter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
11
0
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 11 publications
4
11
0
2
Order By: Relevance
“…More than half of the incidents were attributed to this cause. This supports the findings reported by several previous studies in other countries regarding a higher number of unintentional CO poisoning incidents caused by water heaters (Cho, Chiu, Ho, & Peng, 2008;Duen˜as-Laita et al, 2001;Gajdos et al, 1991). This finding indicates that water heaters represent a serious health threat and needs further attention.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…More than half of the incidents were attributed to this cause. This supports the findings reported by several previous studies in other countries regarding a higher number of unintentional CO poisoning incidents caused by water heaters (Cho, Chiu, Ho, & Peng, 2008;Duen˜as-Laita et al, 2001;Gajdos et al, 1991). This finding indicates that water heaters represent a serious health threat and needs further attention.…”
Section: Discussionsupporting
confidence: 94%
“…It has been estimated that approximately 50,000 annual emergency department (ED) visits in the United States are due to CO poisoning (Hampson & Weaver, 2007). It seems that the mortality and morbidity due to CO exposure is similarly high in other parts of the world (Gajdos et al, 1991;Duen˜as-Laita et al, 2001;Nazari, Dianat, & Stedmon, 2010;Wilson, Saunders, & Smith, 1998).…”
Section: Introductionmentioning
confidence: 97%
“…Specific interpretations of differences in death rates between Taiwan and other countries might not be straightforward. In Taiwan, as in most of the world, the incidence and mortality of acute CO poisoning are probably underestimated because CO poisoning usually leads to nonspecific symptoms that have no helpful unique clinical presentations, which adds to the difficulties for emergency room physicians of recognizing the clinical symptoms of CO poisoning (Duenas-Laita et al, 2001). Thus, the observed differences in the acute CO death rate between Taiwan and other nations could be biased due to differential diagnostic techniques among countries.…”
Section: Trends Of the Annual Mortality Ratementioning
confidence: 80%
“…Sam-Lai et al (2003) investigated causes of household CO poisoning and found that heating systems, mobile heaters, and thermal motors were among the appliances most often involved in accidents. A study by Duenas-Laita et al (2001) reported that the kitchen and bathroom were the two principal CO exposure sites at home, and the majority of the CO poisoning cases were related to malfunctioning of the water heater or central heating. Due to a lack of detailed information regarding how the CO poisoning accidents occurred, we were unable to identify the household-related activities attributable to the increase in the unintentional death rate from CO poisoning in Taiwan. A previous study showed an average annual unintentional CO death rate of 1.7/10 6 py between 1979 and 1988 in California (Girman et al, 1998).…”
Section: Trends Of the Annual Mortality Ratementioning
confidence: 98%
“…Not only do the citizens of our country benefit but also millions of tourists, mainly from Europe, who visit our country each year [5]. Furthermore, as we have seen at the recent Mediterranean congress held in Sitges, Barcelona, scientific activity has increased in volume and in quality, in basic research as well as in fields of clinical interest [6][7][8][9][10][11][12][13][14].…”
mentioning
confidence: 99%